Psychological Safety in Indonesia : Conceptual Analysis and Implications for Indonesia - Danu Kusbandono; Joko Suyono; Hunik Sri Runing Sawitri; Salamah Wahyuni (Universitas 17 Agustus 1945 Semarang, 2025)
Psychological safety, a critical concept in team performance and innovation, remains predominantly studied in developed nations, despite its under-explored relevance in developing countries characterized by rigid hierarchies, collectivist cultures, and socioeconomic disparities. This article analyzes the challenges and opportunities of fostering psychological safety in Indonesia, emphasizing unique dynamics such as paternalistic leadership, deliberative values (musyawarah), and the influence of Pancasila ideology. Through a literature review, critical research gaps are identified: integrating local wisdom, transforming authoritarian leadership systems, and the role of the informal sector. The study advocates for culturally adaptive approaches, empathic leadership training, and leveraging gotong royong (communal cooperation) as a foundation for psychological safety. Theoretical and practical recommendations aim to advance inclusive HR policies and further research in Indonesia, accounting for its sociocultural complexities.